External shocks and business cycle fluctuations in oil-exporting small open economies - Sunday Oladunni (CBN Journal of Applied Statistics, 2019)
This study employs a sign-restricted Bayesian structural vector autoregressive (BSVAR) model to analyse how global demand, oil price and the US monetary policy shocks impact the Nigerian business cycle. The objective is to uncover the dominant external drivers of the business cycle in Nigeria. Results show that global demand and oil price shocks are the principal foreign drivers of the Nigerian business cycle. The global demand shock elicits the strongest responses from output growth and inflation; while oil price shock impacts the terms-of-trade and interest rate the most. The historical contributions of the global demand and oil price shocks to the evolution of output growth are significant and comparable, while that of oil price shock to inflation and interest rate is dominant. Further sensitivity analysis of pre-crisis period of 2008/09 suggests that macroeconomic risk arising from global demand shock is systematic, owing to the comparable impact on output growth and similar interest rate response in the two estimations. Evidence suggests that the GFC may have contributed to the more volatile inflation response to global demand shock in our full sample estimation. Given the strong and pervasive impact of the global demand shock on output growth, Nigeria can manage its vulnerability by shrinking the size of oil exports in its terms-of-trade, while growing non-oil exports progressively through sustained economic diversification and viable industrialisation strategy.
Keywords: F44; E37; C11; E32; 330; External Shocks; Sign Restrictions; Bayesian SVAR; Business Cycle Fluctuation